2020
DOI: 10.1111/cod.13555
|View full text |Cite
|
Sign up to set email alerts
|

Skin reactions of N95 masks and medial masks among health‐care personnel: A self‐report questionnaire survey in China

Abstract: Coronavirus Disease 2019 (COVID-19) was first recognized in December 2019 and was later declared as a pandemic by WHO. Healthcare personnel (HCP) in affected areas were exposed to prolonged use of masks for prevention of infection. This study aims to characterize adverse reactions related to masks among the HCP in China. METHODS A cross-sectional survey was conducted of 583 Chinese HCPs in February 2020, by using a self-administered online questionnaire that was created using a crowdsourcing platform (equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
189
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(218 citation statements)
references
References 5 publications
17
189
1
11
Order By: Relevance
“…In the last few weeks, some articles have been published on cases of dermatitis of the face associated with the use of anti‐COVID‐19 masks 1‐5 . In a Chinese study, it was observed that 49% of subjects reported skin reactions on the face related to mask.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In the last few weeks, some articles have been published on cases of dermatitis of the face associated with the use of anti‐COVID‐19 masks 1‐5 . In a Chinese study, it was observed that 49% of subjects reported skin reactions on the face related to mask.…”
Section: Figurementioning
confidence: 99%
“…Itch (14.9% of patients), erythema (12.6%), and dryness (11.6%) were the most frequent manifestations. Furthermore, 43.6% of patients with acne, 100% of patients with rosacea, and 37.5% of patients with SD reported exacerbation of their diseases 1 . A Polish study demonstrated that itching associated with the use of face mask was present in 19.6% of subjects.…”
Section: Figurementioning
confidence: 99%
“…Inconveniences due to the use of face masks during the COVID-19 pandemic: A survey study of 876 young people Dear Editor, The use of face masks by general population became ubiquitous during the COVID-19 pandemic. 1 Personal protective equipment (PPE) can cause harm to the skin [2][3][4][5] ; however, little is known on inconveniences of face masks wearing. [4][5][6][7] This study was undertaken to analyze the most bothersome issues reported by young people using face protection during current viral pandemic.…”
mentioning
confidence: 99%
“…Recently, authors from China pointed out that 17.1% of HCW developed adverse reactions of respiratory tract due to face mask use. Skin reactions were quite common, including among others, itch (14.9%), redness/erythema (12.6%), rash (12.4%), xerosis (11.6%)burning (3.7%), and pain/prickling (3.2%) 4.…”
mentioning
confidence: 99%
“…A 2012 study showed that mask discomfort due to heat, pressure, and pain signi cantly increases with increased duration of wear, and that discomfort may in uence compliance with protocols for personal protective equipment (2). A survey of healthcare workers in China during the COVID-19 pandemic showed that 22% (90/404) of participants reported discomfort speci cally due to the mask straps, more than any other source of discomfort (1).At rst consideration, this discomfort may seem trivial in comparison to the risks of the pandemic, but this discomfort has been associated with a unwillingness by health care providers to wear isolation masks for the duration of an 8 hour shift even with scheduled breaks (3). This discomfort may potentially decrease compliance with institutional guidelines even among a population of highly educated and motivated providers.…”
Section: Introductionmentioning
confidence: 99%